Structure and function of African swine fever virus proteins: Current understanding - Yang, Sicheng; Miao, Chun; Liu, Wei; Zhang, Guanglei; Shao, Junjun; Chang, Huiyun (Frontiers in Microbiology, 2023)
African swine fever virus (ASFV) is a highly infectious and lethal double-stranded DNA virus that is responsible for African swine fever (ASF). ASFV was first reported in Kenya in 1921. Subsequently, ASFV has spread to countries in Western Europe, Latin America, and Eastern Europe, as well as to China in 2018. ASFV epidemics have caused serious pig industry losses around the world. Since the 1960s, much effort has been devoted to the development of an effective ASF vaccine, including the production of inactivated vaccines, attenuated live vaccines, and subunit vaccines. Progress has been made, but unfortunately no ASF vaccine has prevented epidemic spread of the virus in pig farms. The complex ASFV structure, comprised of a variety of structural and non-structural proteins, has made the development of ASF vaccines difficult. Therefore, it is necessary to fully explore the structure and function of ASFV proteins in order to develop an effective ASF vaccine. In this review, we summarize what is known about the structure and function of ASFV proteins, including the most recently published findings.